PENGARUH PEMBERIAN INDIGOFERA DALAM RANSUM TERHADAP BOBOT HIDUP, GIBLET, DAN LEMAK ABDOMINAL ITIK PEKING - Fadhlurrahman, M. Panji; Nova, Khaira; Septinova, Dian; Riyanti, Rr (JURUSAN PETERNAKAN, FAKULTAS PERTANIAN, UNIVERSITAS LAMPUNG, 2019)
This research to know the impact of Indigofera zollingeriana that wasgiven in rations onliving weight, giblet, and abdominal fat of peking ducks. This research was use completely randomized design (CRD) with 5 treatments and 4 repetitions, every repetitions were consist of 1 duck with a total20 ducks (unsex) with 8,6% diversity. The treatments were given on this research are the R0: 0%, R1: 4%, R2: 8%. R3: 12%, and R4: 16% of Indigofera zollingerianameals. This research was held in the Laboratory Lapang Terpadu of Agriculture Faculty, University of Lampung for 7 weeks from February to April 2018. The variables that observed are livingweight, weight of giblet, and the weight of abdominal fat. The result showed that the impact of Indigofera zollingeriana that was given is not significant (P>0,05) for the of peking ducks. Keywords: Indigofera zollingeriana, living weight, giblet, abdominal fat,peking ducks